Immunological consequences of microbiome-based therapeutics - Alam, Md Zahidul; Maslanka, Jeffrey R.; Abt, Michael C. (Frontiers in Immunology, 2023)
The complex network of microscopic organisms living on and within humans, collectively referred to as the microbiome, produce wide array of biologically active molecules that shape our health. Disruption of the microbiome is associated with susceptibility to a range of diseases such as cancer, diabetes, allergy, obesity, and infection. A new series of next-generation microbiome-based therapies are being developed to treat these diseases by transplanting bacteria or bacterial-derived byproducts into a diseased individual to reset the recipient’s microbiome and restore health. Microbiome transplantation therapy is still in its early stages of being a routine treatment option and, with a few notable exceptions, has had limited success in clinical trials. In this review, we highlight the successes and challenges of implementing these therapies to treat disease with a focus on interactions between the immune system and microbiome-based therapeutics. The immune activation status of the microbiome transplant recipient prior to transplantation has an important role in supporting bacterial engraftment. Subsequently, following engraftment, microbiome transplant derived signals can modulate immune function to ameliorate disease. As novel microbiome-based therapeutics are developed, consideration of how the transplants will interact with the immune system will be a key factor in determining whether the microbiome-based transplant elicits its intended therapeutic effect.